Ma’anil Hadis Perspektif Mustaqim, Ali dan Najwah: Menuju Metode Pemahaman Kontemporer - Mushofa, Chanif; Fathoni, Idzhar (Journal of Hadith Studies, 2020)
Amid modernization, understanding the Prophet's hadiths can no longer rely solely on textual approaches. This study explores the methodological models offered by Abdul Mustaqim, Nizar Ali, and Nurun Najwah. What are their similarities and differences, and how can a new methodology be constructed to meet contemporary challenges? This qualitative research adopts a descriptive-comparative approach. Primary data were sourced from the works of these three scholars and major hadith collections, while secondary data were derived from relevant literature on hadith methodology. The analysis was conducted by comparing their theories and interpretative strategies. The findings reveal that all three employ auxiliary sciences in hadith interpretation, albeit with different emphases. Mustaqim advocates for an interconnection paradigm (socio-historical, anthropological, medical), Nizar Ali proposes six interdisciplinary approaches, while Najwah focuses on historical and hermeneutical methods. Based on this analysis, the author proposes a new method called al-Jam‘u wa al-Ikhtisar, combining linguistic, socio-historical, and scientific approaches as a comprehensive and contextually relevant strategy for hadith interpretation in the modern era.